The Relationship Between Spirituality and Suicide Incidence Among Adolescents: A Literature Review - Eric Dino Tandoyo (SEAN Institute, 2026)
This study aims to systematically review the relationship between spirituality and suicide occurrence in adolescents. A systematic literature search was conducted on PubMed, ScienceDirect, and Google Scholar for articles published between 2013 and 2023. After screening 287 records, 16 observational studies (cross-sectional, cohort, case-control) involving 58,674 adolescents from various countries, including Indonesia, met the inclusion criteria. The majority of studies (13/16) demonstrated a significant negative association between spirituality and suicidal ideation, attempts, and completed suicide. Dimensions of meaning in life and positive religious coping emerged as the strongest protective factors. Spirituality reduced suicide risk by up to 55% through mechanisms of enhanced resilience, hope, moral objections, emotion regulation, and faith-based social support. These protective effects were stronger in highly religious sociocultural contexts. The findings underscore the importance of incorporating spiritual assessment and spiritually integrated interventions into adolescent suicide prevention programs, particularly in settings where religious values are salient. This review provides a comprehensive synthesis of current evidence and highlights the multidimensional role of spirituality as a protective factor against youth suicide.